(untitled) (Bangladesh Journal of Plant Taxonomy, 2006)
The paper deals with 13 taxa belonging to Desmid genus Staurastrum Meyen from some selected areas of Bangladesh. Of these, eight taxa are new records for Bangladesh and two taxa are new to science. Key words: Desmids, Staurastrum, Bangladesh DOI: 10.3329/bjpt.v13i1.592 Bangladesh J. Plant Taxon. 13(1): 41-47, 2006 (June)